PENGARUH PERENDAMAN AIR JERUK NIPIS TERHADAP KADAR FORMALIN DALAM IKAN ASIN TERI NASI - Burhan, Amelia Handayani; Rini, Yuli Puspito; Nurhaeni, Farisya (Media Ilmu Kesehatan, 2018)
Background:The use of formalin as a preservative in salted fish is potentially harmful to the human body,for example in the salted anchovy. They are very popular for customers in Traditional Market of Yogyakarta.The acidic compound, like lime water, can reduce theconcentration of formalin.Objective: This study aims to determine the effect of immersion of lime water on formalin concentration insalted anchovy fish.Methods:A total of 25 samples from five traditional markets of Yogyakarta city were tested using formalin kittest. Positive samples were treated with immersion of lime water with some concentration; 20, 40, 60, 80,and 100% (v/v). Determination of formalin concentration was done by acidimetric method using 0.955Nhydrochloride and methyl red indicator.Results:Concentration of formalin before treatment is 1,397%. The content of Formalin after the immersiontreatment of lime water with concentration 20, 40, 60, 80, and 100% (v/v) for 60 minutes was 1.094; 1,015;0.712; 0.426 and 0.283% (w/w).Conclusion:Based on the statistical test can be concluded that there is the influence of the concentration ofimmersion of lime water to formalin concentration in salted anchovy fish. The higher concentration of limewater can decrease formalin until 79.71%. Keywords:Acidimetric formalin,anchovy salted fish,lemon water,traditional market of Yogyakarta